2007
DOI: 10.1093/eurheartj/ehm027
|View full text |Cite
|
Sign up to set email alerts
|

Pre-procedural predictors of atrial fibrillation recurrence after circumferential pulmonary vein ablation

Abstract: Hypertension and LAD are independent pre-procedural predictors of AF recurrence after CPVA to treat AF. These data may help in patient selection for AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
265
5
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(294 citation statements)
references
References 23 publications
19
265
5
5
Order By: Relevance
“…Females were noted to have higher association to AF recurrence compared with males which again reaffirms the sex‐related variation in outcomes after catheter ablation for AF. Contrary to Berruezo et al23 hypertension was not found to be a predictor of AF recurrence in our study. Additionally, we noted diabetes mellitus and chronic pulmonary disease to be associated with a high likelihood of AF recurrence.…”
Section: Discussioncontrasting
confidence: 99%
“…Females were noted to have higher association to AF recurrence compared with males which again reaffirms the sex‐related variation in outcomes after catheter ablation for AF. Contrary to Berruezo et al23 hypertension was not found to be a predictor of AF recurrence in our study. Additionally, we noted diabetes mellitus and chronic pulmonary disease to be associated with a high likelihood of AF recurrence.…”
Section: Discussioncontrasting
confidence: 99%
“…268,328,329,330 Conversely, patients with pharmacologically controlled hypertension could have similar risk of AF recurrence postablation as those without hypertension. 279 Pooled analysis of two small studies demonstrated that renal artery denervation resulted in both sustained lowering of BP and reduction in AF recurrence postablation.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…328,329,365, 1050,1115,1116,1117 Factors that have been identified as predictors of a poorer outcome, at least in some studies, include (1) non-PAF and particularly long-term persistent AF; (2) sleep apnea and obesity; (3) increased LA size; (4) increased age; (5) hypertension; and (6) LA fibrosis as detected by cardiac MRI. 365 …”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…The size of the left atrium is an important determinant of prognosis (20)(21)(22) and predicts the likelihood of AF recurrence after restoration to normal sinus rhythm (23). It is unclear if LAMAX is a more important predictor of prognosis and response to therapy than traditional measures of left atrial size.…”
Section: Other Clinical Implicationsmentioning
confidence: 99%